Influence of Compressor Station Waste-Heat Recovery Section on Operational Efficiency of Gas Turbine Drive with Isobaric Heat Supply and Regenerative Heat Utilization - A. P. Nesenchuk; V. N. Romaniuk; A. A. Abrazovsky; A. V. Begliak; T. V. Ryzhova; V. V. Begliak; R. O. Kuzmin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The possibility to utilize existing secondary energy resources for heat supply of an industrial enterprise has been proposed on the basis of the analysis on operation of compressor stations of a cross-country gas pipe-line. The paper considers an influence of waste heat recovery section on operational efficiency of gas turbine drive with regenerative heat utilization.